ПРОБЛЕМА ДОСТУПНОСТИ ОБРАЗОВАНИЯ - Шевченко, Л.Я.; Назарова, С.В. (My University, 2019)
Аннотация Данная статья посвящена проблемам доступности образования в Республике Казахстан. Проанализированы основные тенденции в развитии образования в стране, обозначены задачи современного образования. Выделены ориентиры образовательной политики, позволяющие индивидам адаптироваться к социально-экономическим переменам и активно участвовать в социальной жизни. Аbstract This article is devoted to the problems of accessibility of education in the Republic of Ka- zakhstan. The main tendencies in the education development in the country are being analyzed; the objectives of the modern education are described. Education policy signposts are singled out; they assist individuals in adapting to the social and economic changes and in their active participation in the social life.
The problem of accessibility of education
Keywords: высшее образование; глобализация; единое образовательное пространство; система непрерывного образования; профессионализация; адаптация; higher education; globalization; common educational space; system of continuous education; professionilization; adaptation